Network Pharmacology-Based Strategy for the Investigation of the Anti-Obesity Effects of an Ethanolic Extract of Zanthoxylum bungeanum Maxim - Wang, Ying; Yang, Song Hong; Zhong, Keying; Jiang, Ting; Zhang, Mi; Kwan, Hiu Yee; Su, Tao (Frontiers in Pharmacology, 2020)
Network pharmacology is considered as the next paradigm in drug discovery. In an era when obesity has become global epidemic, network pharmacology becomes an ideal tool to discover novel herbal-based therapeutics with effective anti-obesity effects. Zanthoxylum bungeanum Maxim (ZBM) is a medicinal herb. The mature pericarp of ZBM is used for disease treatments and as spice for cooking. Here, we used network pharmacology approach to investigate whether ZBM possesses anti-obesity effects and reveal the underlying mechanism of action. We first built up drug–ingredients–gene symbols–disease network and protein-protein interaction network of the ZBM-related obesity targets, followed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses. The results highlight apoptosis as a promising signaling pathway that mediates the anti-obesity effects of ZBM. Molecular docking also reveals quercetin, a compound in ZBM with the highest degree of connections in the compound-target network, has direct bindings with the apoptosis markers. Furthermore, the apoptotic effects of ZBM are further validated in 3T3-L1 adipocytes and in high-fat diet (HFD)-induced obesity mouse model. These findings not only suggest ZBM can be developed as potential anti-obesity therapeutics, but also demonstrates the application of network pharmacology for the discovery of herbal-based therapeutics for disease treatment.